Temperature‐Responsiveness and Antimicrobial Properties of CNT–PNIPAM Hybrid Brush Films. Issue 4 (11th December 2012) - Pangilinan, Katrina D.; Santos, Catherine M.; Estillore, Nicel C.; Rodrigues, Debora F.; Advincula, Rigoberto C.
Abstract Temperature‐responsive carbon nanotube (CNT)/poly(N‐isopropylacrylamide) (PNIPAM) hybrid brush films were prepared by combining the layer‐by‐layer and surface‐initiated polymerization (LbL‐SIP) techniques. Atom transfer radical polymerization (ATRP) is employed for the preparation of PNIPAM polymer brushes. Antibacterial activity of the CNT/PNIPAM films are investigated against Exiguobacterium sp. AT1b and Exiguobacterium sibiricum strains. Dead assay results show high microbial inactivation on coated surfaces with CNT films, while very low microbial inactivation is observed in PNIPAM films at all temperatures tested. The CNT–PNIPAM films, on the other hand, have antibacterial properties below 32 °C, which is below the lower critical solution temperature (LCST), but allows biofilm formation above the LCST.